Extremely low level of genetic diversity in Gentiana yakushimensis, an endangered species in Yakushima Island, Japan. Issue 5 (12th August 2022) - Ishii, Naohiro I.; Hirota, Shun K.; Tsunamoto, Yoshihiro; Matsuo, Ayumi; Abe, Harue; Suyama, Yoshihisa
Abstract: Rare or endangered species largely contributing to global biodiversity are essential components of ecosystems. Because genetic diversity depends not only on apparent population size but also demographic processes, the conservation priority of endangered species based on population genetics needs to be assessed by comparison with common congeners and demographic events. In this study, we performed population genetic analysis for Gentiana yakushimensis Makino, a rare and endangered plant species with an isolated distribution on Yakushima Island, Japan. We performed comparison of genetic diversity with the congener ( Gentiana triflora Pall. var. japonica [Kusn.] H.Hara), demographic inference, and bottleneck test based on genome‐wide single nucleotide polymorphisms. The result was that G. yakushimensis had an extremely low genetic diversity level and a high inbreeding coefficient level compared with those of the congener. The population of G. yakushimensis was estimated to experience an expansion during the Last Glacial Maximum and a recent bottleneck by the demographic inference and the bottleneck test. Therefore, the low level of genetic diversity of this species might have resulted from the impact of the recent bottleneck and the long‐term maintenance of a small population size. Due to the long lifespan of the genus Gentiana, the current level of genetic diversity probably does not reflect a large part of recent demographic events, which requires long‐term monitoring of changes in genetic diversity to identify the time lag between the reduction in apparent population size and genetic diversity as a future outlook. Abstract : Gentiana yakushimensis, which is endemic to Yakushima Island and endangered, has extremely low level of genetic diversity comparing with common congener. The population of G. yakushimensis estimated to experience the recent bottleneck by demographic inference and bottleneck test.